Fintech and Financial Inclusion: How Digital Payment Systems Empower Small Entrepreneurs - Arianto Dangkeng; Rahim munir (Cendekiawan Indonesia Timur, 2025)
Financial technology (fintech) has revolutionized the financial sector by enhancing accessibility, efficiency, and convenience in financial transactions. One of its most significant contributions is its role in promoting financial inclusion, particularly for small entrepreneurs and micro-enterprises that traditionally face barriers to accessing formal banking services. Digital payment systems, including mobile wallets, peer-to-peer (P2P) lending, and crowdfunding platforms, have enabled small businesses to expand their customer base, improve cash flow management, and participate more actively in the digital economy. This study explores how fintech-driven digital payment systems empower small entrepreneurs by providing financial tools that facilitate transactions, offer alternative credit solutions, and enhance financial literacy. Employing a qualitative research approach, this study examines case studies of small businesses that have integrated fintech solutions into their operations, analyzing the impact on business performance, market reach, and financial sustainability. The findings reveal that digital payment adoption reduces dependency on cash transactions, increases financial transparency, and improves access to microcredit, enabling small entrepreneurs to scale their businesses. Despite these advantages, challenges remain, including digital literacy gaps, cybersecurity risks, and regulatory constraints that hinder broader adoption among small businesses. The study underscores the importance of government policies, financial literacy programs, and fintech-industry collaborations in ensuring the long-term sustainability of fintech adoption for small entrepreneurs. This research contributes to the ongoing discourse on financial inclusion and digital transformation, offering policy recommendations to enhance accessibility, security, and innovation in fintech-driven financial services.